FORMATION OF CULTURE AS THE BASIS OF BEING'S HUMANIZATION - Olena Vasylieva; Mykola Fugelo; Pavlina Fugelo ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
Minimization of the problems that humanity faces today is impossible without the organization and implementation of an effective way of culture development. A civilized person is guided by high moral guidelines and is aware of his or her responsibility for the results of his or her actions. Culture is the most common integral characteristic of a human, a leading generic feature. Outside of culture, a human ceases to be a human. The concepts of culture, spirituality, humanism, humanity, kindness, beauty, harmony are synonymous, they complement each other. Culture that represents such value principles is a significant force for uniting of the world community and its progressive transforming into a community of mutual agreement. Therefore, the development of culture of the rising generation has relation to the global problems of humanity. Based on this fact, the invaluable role of a teacher in this process becomes obvious. Unfortunately, today's reality shows the shortcomings in the training of teachers for educational work. The authors of the article studied the causes of this condition and outlined the ways for their elimination. One of the conditions for the effective development of culture in the applicants for education is an increase in state investments into educational institutions and the state approach to the cultural qualities of the people as the most important capital of the nation.